PENGARUH PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP KESIAPSIAGAAN MENGHADAPI BENCANA LONGSOR LAHAN DI KECAMATAN CIGUDEG KABUPATEN BOGOR - Vini Yuliawati, - (2021)
The potential for landslides in Cigudeg District is dominated by high class. This is the background of the research. In accordance with the potential for land landslides in Cigudeg District, it is necessary for the community to have the knowledge and attitudes in order to improve community preparedness in dealing with landslide disasters. The purpose of this study was to analyze disaster knowledge and preparedness attitudes and to determine the effect of knowledge and attitudes on preparedness to face landslide disasters. The method used in this research is ex post facto quantitative. The sample in this study was the people of Cigudeg District as many as 100 families were taken based on each village. Data collection techniques using literature study, observation, questionnaires/questionnaires, tests, and study documentation. Data analysis techniques in the form of percentage analysis techniques and multiple regression analysis. Based on the research, it was found that the overall knowledge of disaster was in the medium category, and for knowledge based on each village it was in the low to very high category. The overall preparedness attitude is categorized as good, and the preparedness attitude based on each village has a fairly good to very good category. Total preparedness is categorized as almost ready, and for preparedness based on each village has a category from less ready to very ready. the effect of knowledge and attitudes on preparedness to face landslide disasters is 32.2%. This research is useful for the community, local government, and educational practices and knowledge practices in the field of landslide natural disasters to be developed and refined in further studies related to knowledge and attitudes towards preparedness for landslide disasters. Keywords: Preparedness Attitude, Disaster Knowledge, Preparedness